Special drying methods in wood drying / Noorma Theressa Mamat - Mamat, Noorma Theressa (2004)
In this study wood need dried first before we can use it. For this we will considered briefly here the following special drying methods such as boiling in oily liquid, high temperature drying, infrared radiation, vacuum drying, solvent drying, chemical drying, vapor drying and other. At present none of these special drying methods is used extensively, nor are the prospects high for any becoming commercially useful except for rather special applications. High cost and one or more objectionable side effects have limited their wide acceptance for drying lumber. While continued research may extend their use for drying special items, none is likely to render the conventional kiln obsolete.